Design and verification of a measurement setup for wireless remote microphone systems (WRMSs). (3rd January 2022) - Husstedt, Hendrik; Kahl, Julia; Fitschen, Christina; Griepentrog, Sebastian; Frenz, Marlitt; Jürgens, Tim; Tchorz, Jürgen
Abstract: Objective: This work presents the design and verification of a simplified measurement setup for wireless remote microphone systems (WRMSs), which has been incorporated into guidelines of the European Union of Hearing Aid Acousticians (EUHA). Design: Three studies were conducted. First, speech intelligibility scores within the simplified setup were compared to that in an actual classroom. Second, different WRMSs were compared in the simplified setup, and third, normative data for normal-hearing people with and without WRMS were collected. Study sample: The first two studies include 40 older hearing impaired and the third study 20 young normal-hearing adults. Results: Speech intelligibility with WRMS was not different across actual classroom and simplified setup. An analog omnidirectional WRMS showed poorer speech intelligibility and poorer quality ratings than digital WMRSs. The usage of a WRMS in the simplified setup resulted in significantly higher speech intelligibility across all tested background noise levels. Conclusions: Despite being a simplified measurement setup, it realistically emulates a situation where people are listening to speech in noise from a distance, such as in a classroom or meeting room. Hence, with standard audiological equipment, the individual benefit of WRMSs can be measured and experienced by the user in clinical practice.